Polymorphism of the SNP g. 1180 C>T in leptin gene and its association with growth traits and linear body measurement in Kebumen Ongole Grade cattle - Fathoni, A.; Maharani, D.; Aji, R. N.; Choiri, R.; Sumadi, S. (Diponegoro University, 2019)
The aim of this study was to identify the polymorphism of leptin gene and its association with growth traits in Kebumen Ongole Grade cattle. One hundred blood samples were collected for molecular analysis. Polymorphism of the leptin gene was analyzed using Polymerase Chain Reaction - Restriction Fragment Length Polymorphism (PCR-RFLP) with HpyCH4V restriction enzyme and DNA sequencing. Association analysis of the leptin gene with growth traits was analyzed by T-test. The results showed that SNP g. 1180 C>T was found in the population.The SNP changed amino acid from arginine to cysteine. The SNP was significantly associated with a high chest circumference at weaning age in animal having CC genotype (P<0.05). There were two identified alleles, namely C and T, with frequencies were 0.885 and 0.115,respectively. The genotype frequencies of CC, CT and TT were 0.78, 0.21 and 0.01, respectively. Allelic and genotypic distribution in the studied population were in Hardy-Weinbergequilibrium. Animals with CC genotype had a higher circumference at weaning age (WCC) than those with CT genotype. In conclusion, SNP g. 1180 C> T in the leptin gene is potential as genetic marker for growth traits in Kebumen Ongole Grade cattle.